A study of the pharmacological actions of Dioclea grandiflora martius ex bentham - Mattei, Rita; Leite, José Roberto; Tufik, Sérgio (São Paulo Medical Journal, 1995)
Dioclea grandiflora Mart. ex Bent., known as Mucuna or Mucuna of stone, is a member of the Leguminosae family, popularly used for its possible effects on the Central Nervous System (CNS). Reports mention sedative, tonic, and also antiepileptic properties for this plant. In this paper a screening for CNS action was done with aqueous extracts of the seeds. This study was carried out using some animal models for the study of sedative, hypnotic, anxiolytic, anticonvulsivant and neuroleptic activity. The results showed that Dioclea grandiflora Mart. ex Bent. demonstrates the general profile of a CNS depressant drug. However, the extract did not exhibit any of the specific profiles tested. Moreover, the results suggest a possible toxicity stemming from the popular or folk use of this plant.